Perawatan Kuretase Gingiva pada Gigi Premolar Kiri Rahang Atas: Laporan Kasus - Khoman, Johanna A.; Singal, Gabriella A. (e-GiGi, 2020)
Abstract: Periodontal disease has still a high prevalence in the community. It occurs due to the accumulation of plaque or calculus on the tooth surface. The plaque, a thin layer of biofilm, contains a collection of pathogenic microorganisms that cause periodontal tissue and bone disease. The initial treatment of periodontal disease is to eliminate the etiological factors, namely scaling, root planning, and curettage. Curettage is a mechanical cleaning action in periodontitis therapy to remove inflammatory tissue, calculus, and bacterial colonies. This study was aimed to discuss the management of gingival curettage treatment in a 26-year-old female patient who had gingivitis with a 4 mm deep periodontal pocket in her maxillar left premolar, treated with scaling and gingival curettage. Clinical further examination after treatment revealed that the gingiva looked normal without any swelling, and the pocket depth had decreased by about 2 mm.Keywords: periodontal disease, periodontal pocket, gingival curettageÂ Abstrak: Prevalensi penyakit periodontal masih cukup tinggi di masyarakat. Penyakit periodontal diawali ketika plak atau kalkulus terakumulasi pada permukaan gigi. Plak merupakan lapisan tipis biofilm berisi kumpulan mikroorganisme patogen yang menyebabkan kerusakan jaringan periodontal dan tulang. Perawatan awal pada penyakit periodontal ialah dengan menghilangkan faktor etiologi yaitu dengan scalling, root planning, dan kuretase. Kuretase merupakan tindakan pembersihan secara mekanis dalam terapi periodontitis untuk menghilangkan jaringan inflamasi, kalkulus, dan koloni bakteri. Studi ini bertujuan untuk membahas tentang penatalaksanaan perawatan kuretase gingiva pada seorang pasien perempuan berusia 26 tahun yang mengalami gingivitis dengan poket periodontal sedalam 4 mm pada gigi premolar sebelah kiri rahang atas, yang kemudian dilakukan perawatan scalling dan kuretase gingiva. Hasil pemeriksaan klinis perawatan mendapatkan gingiva sudah tampak normal, tidak ada pembengkakan seperti kondisi sebelum kuretase dan kedalaman poket telah berkurang sekitar 2 mm.Kata kunci: penyakit periodontal, poket periodontal, kuretase gingiva